Pengaturan Tentang Ketentuan Sanksi Dalam Peraturan Daerah - Zairin Harahap (Fakultas Hukum Universitas Islam Indonesia, 2006)
Most of by laws consistofpenal sanction whether fine or Imprisonment. It is veryrarely, the enforcement of by laws proposes administrative sanction. Although most of by laws relate to administrative matters. Are by laws not allowed to impose other sanctions, such as administrative sanction ?